Characterization of β-carotene loaded emulsion gels containing denatured and native whey protein. (May 2020) - Lu, Yao; Mao, Like; Zheng, Hongxia; Chen, Hongqiang; Gao, Yanxiang
Abstract: The current study developed whey protein emulsion gels containing β-carotene, and the effects of the content of denatured protein and native protein were investigated. Two sets of emulsion gels were obtained by fixing the total protein content or the denature protein content (Cprotein-D ). Emulsion properties were mostly affected by the content of native protein (Cprotein-N ), and higher Cprotein-N resulted in emulsions with smaller particle size, higher surface charge and better creaming stability. Emulsions were then gelled with the addition of Glucono-δ-lactone. At fixed total protein content, higher Cprotein-D contributed to gels with higher mechanical properties, e.g., fracture stress, Young's modulus and storage modulus (G′). At fixed Cprotein-D, the increase in Cprotein-N also resulted in stronger gels but at much lower magnitude. The dynamic gelation analysis revealed that the increase in Cprotein-N or Cprotein-D resulted in shorter gelling time. All the gels had rather high water holding capacity, and the gels with greater mechanical strength had lower swelling ratios. When emulsion gels were applied as carriers for β-carotene, both Cprotein-D and Cprotein-N had significant effects on the light stability and heat stability of β-carotene. Graphical abstract: Image 1 Highlights: Emulsion gels were prepared with both denatured protein and native protein. Emulsion properties were mostly affected by the content of native protein. The denatured protein played a leading role in the gelation process and structures of the emulsion gels. Both proteins were responsible for the stability of β-carotene.